Community-based development of agricultural activities aiming to improve dietary diversity in Western Kenya [poster] - Boedecker, J.; Termote, Céline; Kennedy, G. (2016)
This research examines the suitability of community-based participatory workshops for developing agricultural activities in order to diversify diets. It represents the second part of a project that consists of a diagnostic phase documenting agricultural biodiversity and nutrition (phase I), participatory development of activities to improve nutrition (phase II) and participatory implementation of the activities (phase III). The study is part of the Agriculture for Nutrition and Health CGIAR Research Program.